Modelo para tomada de decisão nos sistemas produtivos a partir da utilização de uma ferramenta capacidade versus demanda - Barreto, Ronaldo Merlo (Universidade do Vale do Rio do Sinos, 2010)
Considering the frequent changes in the consumer market, companies need to adapt to the new sceneries. Production strategies and capacity can assist in this process, especially if it is possible formulating and testing before applying it in the real plant. The difficulties found by the companies in this business are associated with adjusting (or not) the models found in the literature about the subject, and the information base on which capacity decisions are made. The concepts of production bottleneck and the overall efficiency of resources, and the logic CXD analysis and decision-making are discussed and evaluated throughout the analysis of manufacturing capacity. A Model of Decision-making is proposed, including strategies in different levels: operational – Method Management Routines; tactical - Method Management Improvements, and strategic - Method Management of Long-term Strategic. Through the study of case research methodology, the differences in use of the CXD Tool in different perspectives of decision
Keywords: análise de capacidade e demanda; capacidade de produção; gargalo; recurso com capacidade restrita; tomada de decisão; estratégia de produção; analysis of capacity and demand; bottleneck; capacity constraints resources; decision-making; production capacity; production strategic; Engenharias